Derivation of a parallel string matching algorithm - Misra, Jayadev (Information processing letters, 2003)
We derive an efficient parallel algorithm to find all occurrences of a pattern string in a subject string in O(log n) time, where n is the length of the subject string. The number of processors employed is of the order of the product of the two string lengths. The theory of powerlists [J. Kornerup, PhD Thesis, 1997; J. Misra, ACM Trans. Programming Languages Systems 16 (6) (1994) 1737–1740] is central to the development of the algorithm and its algebraic manipulations.